Lo extraño en la prosa de Juan Ramón Jiménez - Olivé, Laia (Pontificia Universidad Católica del Perú, 2024)
This article reviews and redefines the concept of the uncanny from Todorov’s theory in The Fantastic: A Structural Approach to a Literary Genre (1970) and analyses it in some barely studied prose writings by Juan Ramón Jiménez where it is present. Uncanny literature, which also lacks extensive research, is characterised by the “uncanny effect” it has on the characters and/or the reader: realizing the rarities that intermingle with our everyday life. In Jiménez’s prose, this effect manifests mainly through the compassionate way in which the narrator sees some characters who do not fit into heir environment because of their appearance and/or their behaviour. Among these, we observe children, madmen, sick people, women, foreigners, the incomprehensible and “unacquainted acquaintances”.

Este artículo revisa y redefine el concepto de lo extraño desde la teoría todoroviana en la Introducción a la literatura fantástica (1970), y lo analiza en determinados escritos en prosa de Juan Ramón Jiménez apenas estudiados donde está presente. La literatura extraña, la cual cuenta igualmente con escasa investigación, se tipifica por el “efecto extraño” que causa en los personajes y/o el lector: darse cuenta de las rarezas que se mezclan con nuestra cotidianidad. En la prosa juanramoniana, este efecto se manifiesta principalmente a través de la mirada compasiva del narrador hacia aquellos personajes que por su aspecto y/o comportamiento no encajan con su entorno. Observamos entre estos a niños, locos, enfermos, mujeres, forasteros, incomprensibles y “desconocidos conocidos”.
The Uncanny in Juan Ramón Jiménez’s Prose Work
Keywords: The uncanny; The fantastic; Todorov; Juan Ramón Jiménez; Lo extraño; Lo fantástico; Todorov; Juan Ramón Jiménez; https://purl.org/pe-repo/ocde/ford#6.02.06